(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
This study aims to determine the distribution of Aphis gossypii (Glover) (Hemiptera: Aphidiidae ) on host plants in vegetable agroecosystems lowland and highland South Sumatra. Survey of host plants A. gossypii conducted at 11 sites in South Sumatra vegetable center. Distribution A. gossypii in South Sumatra lowland agroecosystems can be found in Kenten, Soak, Talang Buruk, Tanjungraja, Indralaya and Gelumbang, while in the highlands of South Sumatra agroecosystems colony A. gossypii can be found in Kerinjing , Muarasiban, Pagardin, Bedeng Kresek and Jarai. Distribution A. gossypii very close relation to their host plants that are cultivated plants and wild plants during the dry season and the rainy season. Cultivated plants are colonized A. gossypii mainly of family Cucubitaceae, Solanaceae, Araceae and Apiceae. Wild plants are colonized A. gossypii mainly of family Amaranthaceae, Asteraceae ( Compositae ), Commelinaceae, Ericaceae, Euphorbiaceae, Graminae, Malvaceae, Myrtaceae, Oxalidaceae and Solanaceae. Â Key words: Distribution, Aphis gossypii and Host Plants